Mediated Immediacy and the Distinct Theological Contribution of Christian Experiences of God - Andersen, John Daniel (Journal of pentecostal theology, 2024)
The purpose of this article is to contribute with some analytical philosophical perspectives to Pentecostal theology and the contemporary understanding of Pentecostal experiences of God as ‘mediated immediacy’ to further specify these experiences’ distinct contribution to systematic theology. A trend within Pentecostal theology is to emphasize how Pentecostal experiences are encounters that are theologically interpreted and related to specific beliefs. However, the amount of information and areas of theological knowledge from such experiences need more clarifications. Hence, in Part 1, the author presents four philosophical arguments why experiences of God can contribute to systematic theology with prima facie justified beliefs or theological knowledge. In Part 2, the author proposes that their distinct theological contribution can be specified as manifestation beliefs about God’s doing and being towards a person that represent personal and relational knowledge of God.